Machining Quality Prediction in Stainless Steel Side Milling Using Neural Networks - Ming-Hsu Tsai; Jeng-Nan Lee; Teng-Hui Chen; Tai-Lin Hsu; Dong-Ke Huang (International Journal of Engineering and Technology Innovation, 2026)
This study proposes a novel neural network-based framework to predict machining quality during the side milling of SUS304 stainless steel. As a holistic deep neural network (DNN) framework bridging real-time sensory cutting forces to dual quality metrics—dimensional accuracy and surface roughness—this research addresses a critical gap in SUS304 intelligent machining. A sensory tool holder acquires cutting force signals while an automated in-process system measures machining outcomes. DNN and convolutional neural network (CNN) models are trained using frequency-domain features. Results indicate that the DNN achieves superior robustness, with an average root mean square error (RMSE) of 0.0194 mm for dimensional accuracy and 0.3950 µm for surface roughness. Statistical validation via the mann-whitney u test (p < 0.005) confirms that the DNN more effectively captures global nonlinear relationships within spectral features. This research validates a reliable, high-precision framework for in-process quality prediction, supporting adaptive control in difficult-to-machine materials.